(untitled) (Raparin Journal of Humanities (RJH), 2020)
In general this Research paper examines the biography and personality of Mumtaz Haidari and his role in the history of Kurdish newspapers. All the aspects of the study are supported by proofs, evidence from different trusted sources. The paper expresses its point of views in a very objective way. In all its arguments the writer supports his views and opinions by different sources, in a genuine attempt of him to present a very clear picture of Mr Haidari in all historical incidents of Kurdish history. The research consists of two sections: The first section sheds light on the life of Mr Haidari. The way he grow up and his works up to the present time. The second section focuses on his role in Kurdish newspepars and all his activities and contributions to this fiend.